2018
DOI: 10.1016/j.alcohol.2017.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Differential COMT expression and behavioral effects of COMT inhibition in male and female Wistar and alcohol preferring rats

Abstract: Polymorphisms of the catechol-O-methyl transferase (COMT) gene have been associated with alcoholism, suggesting that alterations in the metabolism of catecholamines may be a critical component of the neuropathology of alcoholism. In the current experiments, the COMT inhibitor tolcapone was utilized in an operant behavioral model of reinforcer-seeking and drinking to determine if this compound was capable of remediating the excessive seeking and drinking phenotype of the alcohol-preferring P rat. Tolcapone was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 59 publications
(84 reference statements)
0
14
0
Order By: Relevance
“…In P rats, tolcapone may diminish the influence that stimuli have over behavior by preventing the metabolism of cortical DA and increasing tone on DA auto receptors. The effect of increased DA would be blunted in Wistars who already exhibit greater levels of extracellular DA coupled with increased expression of COMT in mPFC and therefore a greater capacity to buffer changes in DA efflux (Engleman et al, 2006; McCane et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In P rats, tolcapone may diminish the influence that stimuli have over behavior by preventing the metabolism of cortical DA and increasing tone on DA auto receptors. The effect of increased DA would be blunted in Wistars who already exhibit greater levels of extracellular DA coupled with increased expression of COMT in mPFC and therefore a greater capacity to buffer changes in DA efflux (Engleman et al, 2006; McCane et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…To assess the influence of COMT inhibition on corticostriatal network dynamics, animals were treated with tolcapone (30 mg/kg) or vehicle (counterbalanced) as described previously (McCane et al, 2014, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a single dose of EGCG does not impair the COMT of red blood cells in healthy individuals [77]. A synthetic inhibitor of COMT (tolcapone) reduces the seeking or consumption of ethanol, specifically in male high drinkers [78]. Importantly, phenols can regulate the ratio between CYP enzyme/phase II enzymes, which can be a pivotal phenomenon for the life and death of cells after carcinogens [16].…”
Section: Pharmacokinetics Of Phenols: Influence Of Sex–gendermentioning
confidence: 99%
“…Our group has shown that the COMT val158met SNP plays a role in blood pressure (( Stewart et al, 2009)) and in aripiprazole response in individuals with AUD, in the same direction as DAT1 VNTR effects (( Schacht et al, 2017)). Interestingly, there have been some preliminary reports that COMT inhibitors might have efficacy in some reward-based disorders dependent on COMT val158met genotype both in animals (( McCane et al, 2018)) and in humans ( ( Grant et al, 2013)) suggesting, potentially, an important pharmacogenetic interaction.…”
mentioning
confidence: 99%